Pemberdayaan Ibu-Ibu PKK didesa Rompegading Melalui Pelatihan Daur Ulang Kain Perca Dengan Teknik Patchwork Pada Pembuatan Tas - Asiani Abu; Nurhijrah Nurhijrah; Rika Riwayani (Seminar Nasional LP2M UNM, 2021)
Abstract - Action research, which aims to find out 1) an overview of the implementation of patchwork recycling training with bag-making patchwork techniques in Rompegading Village and 2) the effectiveness of the implementation of patchwork recycling training with patchwork techniques in making handbags in Rompegading Village. The research subjects were PKK women with a total sample of 10 people selected by purposive sampling. Research data obtained by observation, documentation, questionnaires and tests. The data analysis technique used descriptive analysis. The results of this study stated that: 1) the empowerment of PKK women in Rompegading Village through recycling of patchwork with patchwork techniques in making handbags was carried out in three days with seven participants. There are three stages in the implementation of this training, namely: planning/planning, action/implementation and evaluation 2) the effectiveness of patchwork training in bag making seen from learning outcomes, assessment of the training process, performance resultsKeywords: Empowerment, PKK women, training on patchwork recycling, Pachwork technique, bags